Vasculitic multiplex mononeuritis: polyarteritis nodosa versus cryoglobulinemic vasculitis - Steidl, Corinna; Berlit, Peter (Rheumatology international, 2012)
A 76-year-old female patient presented with a progressive motor-sensory multiplex mononeuritis (MM). Combined muscle and nerve biopsy showed the typical findings of a polyarteritis nodosa (PAN). Despite treatment with corticosteroids paresthesias increased and purpura of the legs newly appeared. Hepatitis screening revealed chronic hepatitis C-infection associated with cryoglobulinemia Type II (IgM-kappa Ig A). Finally, we diagnosed a hepatitis C-associated cryoglobulinemic vasculitis based on clinical and laboratory findings.